Assessment of ALK gene rearrangement in lung cancer using a new rapid automated SureFISH (Dako Omnis) assay. Issue 8 (6th March 2017) - Takeda, Maiko; Kasai, Takahiko; Shimizu, Shigeki; Kitaichi, Masanori; Kojima, Kensuke; Nagoya, Akihiro; Hayashi, Akio; Utsumi, Tomoki; Yoon, Hyung-Eun; Matsumura, Akihide; Atagi, Shinji
Abstract : The ALK fluorescence in situ hybridisation (FISH) method is the examination essential for pathological diagnosis and choice of molecular-targeted therapy in ALK -rearranged lung cancer. Here, for detection of ALK gene rearrangement in patients with lung cancer, we evaluated the rapid FISH technology ( ALK SureFISH), a newly developed assay for the automated staining platform Dako Omnis, using 21 formalin-fixed paraffin-embedded (FFPE) samples. All cases could be evaluated with the SureFISH method. SureFISH provided excellent quality signals without any background staining. The SureFISH assay was able to offer a rapid turnaround time (approximately 3.5 hours) and was 100% concordant with prior Vysis FISH results in our laboratory.